Pengaruh Pendidikan, Disiplin Kerja, Motivasi Terhadap Kinerja Pegawai Kantor Kementerian Agama Kota Makassar - Muhammad Alamsyah Ramli; Nasir Hamzah; A. M. Hasbi (Journal of Management Science (JMS), 2021)
The results showed that education has less influence on the performance of the employees of the Office Kementerian Agama Kota Makassar. Meanwhile, the variable work discipline, motivation has a positive and significant effect on the performance of the employees of the Office Kementerian Agama Kota Makassar. From the results of regression testing, it is known that the dominant variable that affects the Employee Performance of the Office Kementerian Agama Kota Makassar.